Development of a measure to assess the perceived illness experience after treatment for cancer. Issue 4 (April 1995) - Eiser, C; Havermans, T; Craft, A; Kernahan, J
Abstract : The development of a scale to measure perceived illness experience in young people with cancer is described. Areas of concern were first identified through semistructured interviews conducted with children and adolescents. As a result, 78 items were generated to cover the main areas identified (physical appearance, interference with activity, peer rejection, integration in school, manipulation, parental behaviour, disclosure, preoccupation with illness, and impact of treatment). These items were rated (on five point scales) by 41 patients (mean age 14.6 years) and 35 of their parents. Measures of physical functioning (symptoms, functional disability, and restrictions) and psychological functioning (symptoms) were included for validation purposes. Test-retest reliability was calculated on the basis of ratings made by a subsample of parents on two separate occasions. A 34 item scale was constructed with four items in each of the areas identified above, except for physical appearance (n = 2). The scale has adequate internal reliability and validity. There were significant correlations between parents and their children on all subscales except for illness disclosure and impact of treatment, suggesting that parents may be less reliable informants for their children in these contexts. The scale has potential use in clinical contexts, in evaluating the psychosocial impact of different treatment regimens, and as an outcome measure in intervention work.